IMPROVING KNOWLEDGE ABOUT EARLY DETECTION AND SCREENING OF BREAST CANCER AMONG FEMALE RESIDENTS IN GANDUL VILLAGE, PILANGKENCENG DISTRICT, MADIUN REGENCY - Alphania Rahniayu; Gondo Mastutik; Anny Setijo Rahaju; Nila Kurniasari; Khafidhotul Ilmiah; Wira Santoso Ongko (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: Breast cancer is still a burden by being the most frequent malignancy and the highest cause of cancer death in women. The death rate from breast cancer can be reduced by early case finding and appropriate immediate treatment. Early case finding can be started with a simple periodic examination that can be carried out by each individual independently, namely by breast self-examination. This study aims to determine the effect of education on early detection and screening of breast cancer on the level of knowledge among women in Gandul village, Madiun district. Methods: This study involved 101 participants aged from 25 to 87 years old, including female residents of Gandul village and cadres of public health center.Â  We conduct health education about breast cancer and early detection of breast cancer, especially regarding breast self-examination. Pre-test and post-test were also conducted to assess the the knowledge of the participants before and after the seminar held. Results: The pre-test score of participants with low scores (<75) was 78.21% (79 people) and decreased in the post-test to 43.56% (44 people), while participants with high scores (>75) were only 21.78% (22 people) in the pre-test and increased to 56.44% (57 people) in the post-test. Conclusion: There is a knowledge improvement about the early detection of breast cancer among participants after the intervention. The knowledge improvement can be seen through the increased score from pre-test to post-test.